Revision of the deep-sea Eulimidae (Gastropoda, Caenogastropoda) from off Northeast Brazil - de Souza, Leonardo Santos; Pimenta, Alexandre Dias; de Barros, José Carlos Nascimento (Zootaxa, 2021)
The present study reviews the taxonomy of the marine gastropods belonging to the family Eulimidae Philippi, 1853 from the continental slope off Northeast Brazil. The genera Abyssoaclis Barros, Mello, Barros, Lima, Santos, Cabral & Padovan, 2003 and Aclis Lovén, 1846 were not treated here. A total of 20 taxa were identified in this region, excluding Eulima hebes Watson, 1883, a species with a doubtful classification in Eulimidae. The species were assigned to the following genera: Costaclis Bartsch, 1947, Eulima Risso, 1826, Fusceulima Laseron, 1955, Melanella Bowdich, 1822, Ophieulima Warén & Sibuet, 1981, Sticteulima Laseron, 1955, Thaleia Warén, 1979, and Umbilibalcis Bouchet & Warén, 1986. The genera Sticteulima, Ophieulima and Umbilibalcis are reported for the first time in the southwestern Atlantic. Four species represent new records for the southwestern Atlantic. A redescription of the shell morphology is provided for: Costaclis egregia (Dall, 1889b), Melanella doederleini (Brusina, 1886), and Umbilibalcis lata (Dall, 1889b). Additional information to the original description are reported for other species. Melanella sarissa is considered as a synonym of Melanella cinca Dall, 1927. Six new species are described: Eulima cracentis sp. nov., Melanella paraabida sp. nov., M. adiastalta sp. nov., M. anapetes sp. nov., Sticteulima cabrali sp. nov. and S. canopusensis sp. nov. Lectotypes are designated for: Costaclis hyalina, C. egregia, Eulima ephamilla (Watson, 1883), E. psila and E. (?) hebes. Eulima sp. 1, Melanella sp. 1 and Melanella sp. 2 are potential new species, but the scarcity of material precludes a formal description at this moment.